A colour handbook acute adult dermatology diagnosis and management - Creamer, Daniel (Manson, 2011)
It is sometimes reckoned, by the ill-informed, that skin disease does not present acutely. This is quite untrue. A significant proportion of skin disease develops rapidly, is highly symptomatic, and can be associated with considerable morbidity.